Effect of Packing Parameters and Gate Size on Shrinkage of Aspheric Lens Parts - 胡广洪 崔振山 (Shanghai jiao tong da xue xue bao, 2010)
In order to produce the high quality optical aspheric lens, the shrinkage of lens should be strictly controlled during the injection process. Serials of experiments are done to find the factors that affect the lens shrinkage during the injection molding process. The study is focused on the effect of gate size, packing time and pressure on the shrinkage. The gate size decides the effective packing time. Only when the effective packing time is enough, the shrinkage size will be decreased along with the packing pressure increased. However the packing time is determined by the gate size. But big gate size is not easily to be cut and the cutting difficulty will cause the part quality problems. The experiments show that packing pressure not only determines the part shrinkage size and also affects the part shrinkage uniformity. When the packing pressure is more than a critical one, the effect of packing pressure on the shrinkage size becomes smaller. And the shrinkage uniformity is guaranteed.